A helping hand for thinking and speaking: Effects of gesturing and task planning on second language narrative discourse. (July 2020) - Lin, Yen-Liang
Abstract: While a growing body of research has provided important insights into the facilitative roles gesturing and task planning play in thinking and speaking, their synergistic effects on second language narrative discourse are not yet well understood. This study examines how different planning conditions, pre-task planning (PTP) and on-line planning (OLP), influence gesture forms and functions in narrative tasks, and how active gesturing influences narrative discourse planning and story organization. It was found that deictic gestures and overall representational gestures were used significantly more in OLP, while iconic gestures were used significantly more in PTP. Gesture functions fall into four categories: activating, manipulating, packaging, and exploring. Activating was the most common function in both OLP and PTP groups, while manipulating and exploring were used significantly more in OLP than in PTP. These findings provide evidence of self-oriented functions of gestures in an L2 narrative task that is cognitively demanding in conceptualization and formulation. Furthermore, the L2 learners in this study who were free to use gestures when they re-told stories produced more complete episodes and relevant propositional information than those who were restricted from doing so, showing the potential facilitative cognitive effects of gestures on discourse planning and information retrieval.